A Comprehensive Study of Digital Image Steganography: Techniques, Applications and Security Challenges in Covert Communication - Vinay siwach; Rahul Kaushik (International Journal of Advanced Research and Multidisciplinary Trends (IJARMT), 2026)
Digital image steganography has emerged as a crucial technique in the field of secure communication, enabling the concealment of sensitive information within digital images in a manner that is imperceptible to human vision. Unlike cryptography, which focuses on encrypting the content of a message, steganography emphasizes hiding the very existence of the message, thereby providing an additional layer of security. With the rapid growth of digital communication and the widespread use of multimedia content, the demand for covert communication methods has increased significantly. This study presents a comprehensive analysis of digital image steganography, focusing on its core concepts, various embedding techniques, practical applications and associated security challenges. It examines traditional methods such as Least Significant Bit (LSB) substitution, transform domain techniques including Discrete Cosine Transform (DCT) and Discrete Wavelet Transform (DWT), as well as modern approaches that integrate machine learning and deep learning for improved performance. The study also explores evaluation parameters such as payload capacity, imperceptibility and robustness, which are critical in determining the effectiveness of steganographic systems. Furthermore, it highlights potential threats such as steganalysis, data distortion and attacks that aim to detect or disrupt hidden communication. The findings indicate that while digital image steganography offers a powerful means of secure and covert communication, it also faces significant challenges in maintaining a balance between data hiding capacity, security and resistance to detection. The paper concludes by emphasizing the need for more advanced, adaptive and robust steganographic techniques to address emerging security concerns in the evolving digital landscape.